Defining the Organization of Municipal Solid Waste Management Based on Production Costs - Massimo Beccarello; Giacomo Di Foggia (Urban Science, 2023)
A long-lasting dilemma on the efficient provision of services of general economic interest has become increasingly important in the waste management industry: competition or monopoly in municipal solid waste management. Previous literature has primarily examined the economics of scale and scope to provide an adequate response. Here, we contribute by investigating subadditivity in municipal solid waste management service costs. Subadditivity is a critical concept used to justify imperfect competition, which encourages natural monopolies where one producer will function more effectively than more firms. To test the hypothesis that a subadditivity in costs in waste management exists, we design a simulation based on empirical data for Milan, Italy. We compared the total production cost of the incumbent firm with the alternative hypothesis built by dividing the city into four areas and assigning each area to a different hypothetical firm. The results suggest that the existence of subadditivity results in 6% lower production costs, primarily stemming from business synergies, lower transactional costs, and optimization of productive resources and facilities. The evidence justifies, ceteris paribus, that the provision by a single firm is preferable to multiple firms in the analysis case. Implications for policies are straightforward. The one-fit rule approach fails to set the best condition for policymakers to create a level playing field transparently and efficiently for industry operators to perform efficiently.
Keywords: L8; Q5; 330; waste management; Cost efficiency; economies of scale; urban economy